2007
DOI: 10.1007/s10750-006-0477-5
|View full text |Cite
|
Sign up to set email alerts
|

Feeding ecology of gray whales inferred from stable-carbon and nitrogen isotopic analysis of baleen plates

Abstract: Stable-carbon and nitrogen isotopic compositions (d 13 C, d 15 N) of baleen plates of two juvenile and four adult gray whales (Eschrichtius robustus) were examined. High variance in isotopic composition of baleen plates was detected among individuals and, unlike other migratory species of baleen whales examined isotopically, d 13 C and d 15 N values of most whales showed no regular oscillations. Only one baleen plate reflected the assumed principal Arctic prey (ampeliscid amphipods) during growth on the summer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
25
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 39 publications
5
25
0
Order By: Relevance
“…Protocols for BSI analysis are published elsewhere (Eisenmann et al, 2016). In brief, blubber samples were extracted overnight in a 2:1 chloroform:methanol solution to remove any oils and lipids (Caraveo-Patiño, Hobson, & Soto, 2007;Hobson & Schell, 1998) and oven-dried at 58°C. 1-2 mg of clean sample material were weighed into tin capsules for isotope analysis (Caraveo-Patiño et al, 2007).…”
Section: Bulk Stable Isotope Analysismentioning
confidence: 99%
“…Protocols for BSI analysis are published elsewhere (Eisenmann et al, 2016). In brief, blubber samples were extracted overnight in a 2:1 chloroform:methanol solution to remove any oils and lipids (Caraveo-Patiño, Hobson, & Soto, 2007;Hobson & Schell, 1998) and oven-dried at 58°C. 1-2 mg of clean sample material were weighed into tin capsules for isotope analysis (Caraveo-Patiño et al, 2007).…”
Section: Bulk Stable Isotope Analysismentioning
confidence: 99%
“…Within the context of marine environments, archeologists have used stable carbon isotope analysis to reconstruct the relative contributions of terrestrial versus marine resources to mixed human diets (e.g., Coltrain, 2009;Coltrain et al, 2004;Lovell et al, 1986;McGovern-Wilson and Quinn, 1996 [but see Ambrose et al, 1997]; Parkington, 1988Parkington, , 1991Richards and Hedges, 1999;Sealy, 1986;Sealy and van der Merwe, 1985, 1986, 1988Walker and DeNiro, 1986). This method has also been used to track migration and foraging patterns of several Arctic species including bowhead whale, anadromous fish, migratory waterfowl and pinnipeds (e.g., Bunn et al, 1989;Burton and Koch, 1999;Caraveo-Patiño et al, 2007;Dehn et al, 2007;Hobson, 1987;Hobson and Welch, 1995;Kling et al, 1992;Tamelander et al, 2006;Wada et al, 1991). In the case of human foragers subsisting on marine resources, stable carbon isotope values can also covary with foraging environment.…”
Section: Stable Carbon Isotopesmentioning
confidence: 99%
“…Previous studies have shown that stable isotope ratios along baleen plates provide insight into seasonal movements between feeding grounds (Schell et al 1989a, b;Hobson and Schell 1998;Caraveo-Patiño et al 2007;Bentaleb et al 2011;Ryan et al 2013;Eisenmann et al 2016). For instance, the seasonal shift in stable isotope values evident in Southern right whale (Eubalaena australis) baleen indicates an annual migration over the south Atlantic convergence (Best and Schell 1996).…”
Section: Introductionmentioning
confidence: 99%